MACROECONOMIC DETERMINANTS AND STOCK MARKET VOLATILITY ADMIST THE PERIOD OF ECONOMIC RECESSION IN NIGERIA - Hauwa Bayero TIJJANI; Prof Sheikh Ahmad Abdullahi; Dr Ibrahim Mohammed; Dr Isma’il Tijjani Idris (Gusau Journal of Accounting and Finance)
The goal of liberalizing the Nigerian stock market was to improve its performance and increase market efficiency. Nonetheless, it appears that the onset of Nigeria's 2016 economic downturn has skewed the degree to which these macroeconomic factors influence volatility on the Nigerian Stock Exchange. Using monthly data from February 2010 to September 2022, the study investigated how the economic slump affected the connection between macroeconomic factors and stock market volatility in Nigeria. The exchange rate and stock market liberalization are the macroeconomic factors that are being studied. The time series data was subjected to the Philip Perron (PP) and Augmented Dickey Fuller (ADF) unit root tests. The ARCH LM tests was also carried out and the EGARCH model was estimated under the assumption on normally distributed. The ARCH tests results revealed that there exists ARCH effects in the NGX stock returns implying the presence of volatility clustering in the return series. The findings also showed that the relationship between macroeconomic factors and stock market volatility is negatively impacted by economic recession. It was discovered that the exchange rate had little effect on volatility. It was also shown that liberalization of the stock market significantly reduced volatility. The results also show that there is persistent volatility in the Nigerian stock market and that negative news causes more volatility than positive news of the same size. It is recommended that authorities develop regulations aimed at reviving investor faith in the market.